Implementasi Model Pembelajaran Cooperatif Learning Dengan Media Konkret Untuk Meningkatkan Hasil Belajar Muatan Pelajaran Matematika Siswa Kelas I SD Negeri 1 Seraya Barat - Ni Nengah Suwarningsih (Jayapangus Press, 2021)
This classroom action research was carried out in two cycles with the aim of improving the learning outcomes of mathematics lessons for Class I students of SD Negeri 1 Seraya Barat. The subjects of this study were Class I students of SD Negeri 1 Seraya Barat with a total of 30 students consisting of 13 female students and 17 male students. Data were collected using the test method. The collected data was then analyzed by qualitative descriptive statistics. The results of the study show that the implementation of cooperative learning models with concrete media can improve learning outcomes for mathematics lessons. The success of implementing cooperative learning models with concrete media can be seen from the learning process that is more active for students. All students were actively involved in taking turns demonstrating counting division and enthusiastically presenting the results of their work, namely calculating the division of natural numbers in front of the class according to the questions that had been selected. The implementation of cooperative learning models with concrete media is carried out using the help of straws, plastic cups and folding paper. The success of implementing cooperative learning models with concrete media is also evidenced by the increase in the average value of learning outcomes achieved at the end of the first cycle, which is 74.89 and the average value of learning outcomes achieved at the end of the second cycle, which is 86.44. Based on these results, the average value of learning outcomes from cycle I to cycle II increased by 11.55. The percentage of students who achieved KBM from cycle I to cycle II also increased by 26.66%, from 66.67% to 93.33%.